1997
DOI: 10.1007/bf02815160
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial membrane fluidity and oxidative damage to mitochondrial DNA in aged and AD human brain

Abstract: Oxidative damage on biological molecules has been proposed as a major cause of alterations observed in aging brain as well as in neurodegenerative diseases. In this study, we measured membrane fluidity in mitochondria extracted from three cerebral regions and cerebellum of Alzheimer disease (AD) patients and age-matched controls by means of fluorescence polarization technique. A significant reduction of mitochondrial membrane fluidity was found in AD, except in cerebellum. In controls, a decrease of membrane f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(102 citation statements)
references
References 44 publications
2
98
0
2
Order By: Relevance
“…Mecocci et al found a small but significant increase in oxidative damage to nDNA in patient brain samples and a highly significant threefold increase in oxidative damage to mtDNA in AD compared with agematched controls [11] . Later, the same authors found a significant reduction of mitochondrial membrane fluidity in AD [12] . 4.…”
Section: Sugars: An Increased Glycation and Glycoxidationmentioning
confidence: 82%
“…Mecocci et al found a small but significant increase in oxidative damage to nDNA in patient brain samples and a highly significant threefold increase in oxidative damage to mtDNA in AD compared with agematched controls [11] . Later, the same authors found a significant reduction of mitochondrial membrane fluidity in AD [12] . 4.…”
Section: Sugars: An Increased Glycation and Glycoxidationmentioning
confidence: 82%
“…Incomplete reduction of oxygen increases ROS, which are known to impair the structural integrity of the inner mitochondrial membrane result in a reduction of the efficiency of the electron transport chain. 38 Furthermore, increased ROS oxidizes both proteins and DNA thus promoting apoptosis. 39 In addition to the potential central nervous system toxicity from increased ROS generation, increasing oxygenation could also lead to cerebral vasoconstriction, resulting in reduced perfusion in the brain.…”
Section: Mitochondrial Dysfunction and Normobaric Oxygenmentioning
confidence: 99%
“…For example, recent studies have demonstrated a decline in polyunsaturated fatty acids (PUFA) [19,20], increased levels of lipid peroxidation markers [19,21,22], as well as protein oxidation [23,24], DNA oxidation [25][26][27] and RNA oxidation [28][29][30][31] during AD. Additionally, the presence of oxidative stress markers such as advanced glycation end products (AGE), glycoxidative end products, e.g., N ε -carboxymethyllysine and lipid peroxidation adducts are detected in both NFT and senile plaques in AD [21][22][23][24][32][33][34][35] Interestingly, our recent finding demonstrated ultrastructural features of vascular lesions and mitochondria in brain vascular wall cells from human AD brain biopsy are also suggestive of oxidative damage [45,46].…”
Section: Vascular Oxidative Stress In Alzheimer Diseasementioning
confidence: 99%